Environmental Drivers of Diversification and Hybridization in Neotropical Butterflies - Rueda-M, Nicol; Salgado-Roa, Fabian C.; Gantiva-Q, Carlos H.; Pardo-Díaz, Carolina; Salazar, Camilo (Frontiers in Ecology and Evolution, 2021)
Studying how the environment shapes current biodiversity patterns in species rich regions is a fundamental issue in biogeography, ecology, and conservation. However, in the Neotropics, the study of the forces driving species distribution and richness, is mostly based on vertebrates and plants. In this study, we used 54,392 georeferenced records for 46 species and 1,012 georeferenced records for 38 interspecific hybrids of the Neotropical Heliconius butterflies to investigate the role of the environment in shaping their distribution and richness, as well as their geographic patterns of phylogenetic diversity and phylogenetic endemism. We also evaluated whether niche similarity promotes hybridization in Heliconius. We found that these insects display five general distribution patterns mostly explained by precipitation and isothermality, and to a lesser extent, by altitude. Interestingly, altitude plays a major role as a predictor of species richness and phylogenetic diversity, while precipitation explains patterns of phylogenetic endemism. We did not find evidence supporting the role of the environment in facilitating hybridization because hybridizing species do not necessarily share the same climatic niche despite some of them having largely overlapping geographic distributions. Overall, we confirmed that, as in other organisms, high annual temperature, a constant supply of water, and spatio-topographic complexity are the main predictors of diversity in Heliconius. However, future studies at large scale need to investigate the effect of microclimate variables and ecological interactions.